Can parentage analysis facilitate breeding activities in root and tuber crops? - Norman, P.E.; Asfaw, A.; Tongoona, P.B.; Danquah, A.; Danquah, E.Y.; Koeyer, D. de; Asiedu, Robert (MDPI, 2018)
Controlled pollination in root and tuber crops is challenging. Complex ploidy, cross-incompatibility, erratic flowering patterns, outcrossing, etc., limit the efficiency of breeding progress in these crops. Half-sib breeding that involves random pollination among parents is a viable method to harness genetic gain in outcrossing crops that are problematic for performing planned and controlled pollination. The authenticity of resulting progenies from the half-sib breeding is essential to monitor the selection gain in the breeding program. Parentage analysis facilitated by molecular markers is among the available handy tools for crop breeders to maximize genetic gain in a breeding program. It can help to resolve the identity of half-sib progenies and reconstruct the pedigree in the outcrossing crops. This paper reviews the potential benefits of parentage analysis in breeding selected outcrossing root and tuber crops. It assesses how paternity analysis facilitates breeding activities and the ways it improves genetic gain in the root and tuber breeding programs. Conscious use of complementary techniques in the root and tuber breeding programs can increase the selection gain by reducing the long breeding cycle and cost, as well as reliable exploitation of the heritable variation in the desired direction.